Sterile Leukocyturia Is Associated With Interstitial Fibrosis and Tubular Atrophy in Kidney Allograft Protocol Biopsies. Issue 4 (12th February 2014) - Coelho, S.; Ortíz, F.; Gelpi, R.; Koskinen, P.; Porta, N.; Bestard, O.; Melilli, E.; Taco, O.; Torras, J.; Honkanen, E.; Grinyó, J. M.; Cruzado, J. M.
<x xml:space="preserve">Abstract</x> Kidney allograft interstitial fibrosis and tubular atrophy (IF/TA) is associated with a poorer renal function and outcome. In the current clinical practice, an early diagnosis can only be provided by invasive tests. We aimed to investigate the association of sterile leukocyturia with Banff criteria histological findings in kidney allograft protocol biopsies. We studied 348 allograft biopsies from two different European countries performed at 8.5 + 3.5 months after transplantation. In these cases, the presence of sterile leukocyturia (Leuc+, n = 70) or no leukocyturia (Leuc−, n = 278) was analyzed and related to Banff elementary lesions. Only IF/TA was significantly different between Leuc+ and Leuc− groups. IF/TA was present in 85.7% of Leuc+ and 27.7% of Leuc− patients (p < 0.001). IF/TA patients had higher serum creatinine and presence of proteinuria (p < 0.05). Independent predictors of IF/TA were donor age, donor male sex, serum creatinine and Leuc+ (hazard ratio 18.2; 95% confidence interval, 8.1–40.7). The positive predictive value of leukocyturia for predicting IF/TA was 85.7% whereas the negative predictive value was 72.3%. These studies suggest that leukocyturia is a noninvasive and low‐cost test to identify IF/TA. An early diagnosis may allow timely interventional measures directed to minimize its impact and improve graft outcome.